Concussion guideline implementation perceptions and experiences among parents of community-level Australian Football junior players. Issue 1 (23rd April 2017) - White, Peta E; Register-Mihalik, Johna; Donaldson, Alex; Sullivan, S John; Finch, Caroline F
Abstract : Background/aim: Concussion guidelines exist for multiple community sports. Parents are key stakeholders in guideline implementation and in appropriate responses following concussive injury. The purpose of this qualitative investigation was to understand how parents of community-level Australian Football (AF) players experience and perceive concussion guidelines in order to inform the design and implementation of concussion guidelines in community sport. Methods: A cross-sectional qualitative approach was adopted to allow for an open and detailed exploration of the views of parents of junior community AF players (ie, those aged <16 years) regarding concussion guidelines of the AF League (AFL)—the national governing body for AF. Participants were 15 parents of junior community AF players from two clubs affiliated with a large regional community AF League. Results: The key experiences and perceptions of the parents included appreciation that the guidelines outlined the postconcussion process that should be followed, desires for better understanding of the guidelines by general practitioners (ie, medical doctors) who care for children with concussion, having more readily available information for parents and receiving more formal policy guiding timing of return-to-participation following concussion. Difficulties with the guidelines not addressing delayed presentations of concussion were also frequently mentioned. Conclusions: Parents are key stakeholders in concussion prevention and care in community sport. As such, their input should be considered when developing guidelines and resources for community sport. Furthermore, concussion information should be made available to parents in an easily accessible and community-friendly form.